The multivariate dynamic causal relations between financial depth, inflation, and economic growth - Pradhan, Rudra P. (Philippine Review of Economics, 2017)
This paper examines the dynamic causal relationship between financial depth, inflation and economic growth in India and Pakistan using an autoregressive distributive lag bounds testing procedure and vector error correction modeling approach. The paper uses three proxies for financial depth: broad money supply; domestic credit to private sector; and domestic credit provided by the banking sector. The results of this study prove that financial depth, inflation, and economic growth are cointegrated, indicating the presence of a long-run equilibrium relationship between these variables. The study also finds that financial depth, inflation, and economic growth are Granger-causing each other. It is therefore recommended that both India and Pakistan should intensify their financial depth in order to increase economic growth and reduce inflation.